Aplikasi Andrich Rating Scale Model Pada Analisis Psikometrik Tes Uraian Kimia Dasar I - Anggi Ristiyana Puspita Sari; Rizki Nor Amelia; Sri Rejeki Dwi Astuti; Dian Normalitasari Purnama (Jurnal Ilmiah Kanderang Tingang, 2023)
General Chemistry I is a compulsory subject taken by preservice science teachers where concept mastery of the subject can be explored through an essay test. The purpose of this study was to describe the psychometric characteristics of the General Chemistry I essay test using the Andrich Rating Scale Model by the Winsteps program. The research was conducted in the Odd Semester of the 2022/2023 Academic Year involving 46 students who were selected through a cluster random sampling technique. Although the results of the psychometric analysis showed that the rating scale had not functioned as it should, the General Chemistry I essay test instrument proves to have good (unidimensional) construct validity with all items in the category of moderate difficulty level. This research at the same time proves that it is not easy to make and define categories in an essay test. The use of the Andrich Rating Scale Model provides very useful information for describing and improving the psychometric quality of essay tests on measuring the General Chemistry I ability of preservice science teachers.